Specifics of Participation of Industrial Companies of the Railway Transport in Ukraine in Functioning of Innovation-Oriented Industrial Logistic Clusters - Dikan, Olena; Polyakova, Olena; Ustenko, Marina; Shramenko, Olena; Rekun, Anna (International Journal of Engineering and Technology, 2018)
The article reveals the specifics of participation of industrial companies of the railway transport of Ukraine in the process of functioning of innovation-oriented industrial logistic clusters. The interpretation of the concept of a cluster and definition of its main components has been studied. The problems and prospects of development of industrial companies of railway transport of Ukraine have been studied. It has been determined that the new model of economic development of industrial companies of the railway industry should be based on interaction of all the participants involved at all stages of the life cycle of creating innovative products by forming innovation-oriented industrial-logistic clusters. It has been noted that innovation engineering centers that initiate and develop innovations and coordinate the entire innovative process of product creation are the core of innovation-oriented industrial logistic clusters.The main problems that hinder the use of the cluster approach in management of regional systems in Ukraine have been revealed and active participation of the state in creation of conditions for development of innovations, cooperation of the state, science and business and creation of the national innovation infrastructure has been justified.Â Â